Legal Certainty of Actio Pauliana Decision in Bankruptcy Cases - Ruth Irene Saurmauli (LOCUS MEDIA PUBLISHING, 2022)
In bankruptcy practice, it is not uncommon for debtors to try to reduce bankruptcy assets by performing legal actions against their bankruptcy assets, resulting in losses for creditors. To protect the rights of Creditors, actio pauliana is an instrument provided by law. For example, in the case of Decision Number 1 / Pdt. Sus - Actio Pauliana / 2018 / PN. Niaga.Mdn Jo Supreme Court Decision Number 89K / Pdt. Sus - Bankruptcy / 2019 / PN. Mdn where the Panel of Judges rejected the Cassation request with the consideration that the evidence submitted could not prove that the bankrupt debtor knew or should have known that the sale and purchase would harm the creditor. However, as a result of the sale and purchase made by the debtor with a third party, the bankruptcy estate was reduced, to the detriment of the creditors. Therefore, the purpose of the research was held to find out and analyze actio puliana can provide legal protection carried out by the curator against creditors, the limitations between good faith debtors and bad faith debtors in transferring part of the bankruptcy property and the application of actio pauliana law by the Panel of Judges. This research uses normative juridical research with a legislative approach, case approach and legal doctrines. The results of the research found that actio pauliana is a form of legal certainty over the rights of creditors in bankruptcy. In the actio pauliana lawsuit, it is necessary to have criteria for good faith debtors and bad faith debtors. If it can be proven that the legal action was carried out in bad faith and is detrimental to the creditors, then the actio pauliana lawsuit is rejected and the decision to reject from the Panel of Judges makes no cancellation of legal actions carried out by the bankrupt debtor.